(untitled) (Research, Society and Development, 2022)
The “cajuí” is a fruit originated from the “cajuizeiro” (Anacardium spp), a plant belonging to the family Anacardiaceae native to the northeastern region of Brazil, which can also be found in the north and center-west areas. Cashew is smaller compared to cashew (Anacardium occidentale) and both are found predominantly in the “cerrado” ecosystem. The “cajuí” is much appreciated in the cuisine in its form, juices, liqueurs, ice cream and jellies, and much used in the manufacture of cosmetics, besides being essential for the economy of Tocantins, being marketed in supermarkets and local fairs. This work aimed at the physical, chemical-chemical and volatile Araguaína “cajuí”. From the last year, the Federal University of Tocantins (UFT), Araguaína campus, Cimba unit, during the period from August 2017 to November 2018. During the months of August, September, October and November 2008, the four Campus cashew nuts were collected and frozen for further analysis. The cashews were the following figures: complete physical weight, weight, total titratable acidity (ATT), ash, moisture and volatile profile. The results have shown that the fruit studied in the UFT has its physical-chemical and aromatic properties, indicating differences between the cashew and the volatile chemical volume and the dimensions of size and weight among the cashew nuts of the different cashew trees.